SOCIAL AWARENESS IN AN INDONESIAN JUNIOR HIGH SCHOOL ENGLISH TEXTBOOK - Chelsea Victoria Martan; Imam Santosa (Journal of Language and Literature, 2026)
Social awareness is a central component of Social and Emotional Learning (SEL) because it supports empathy, perspective-taking, respect for diversity, and responsible participation in social life. In English language education, textbooks function not only as linguistic resources but also as carriers of social and interpersonal values. However, previous studies have more often examined moral or cultural values in general than the specific representation of social awareness in English textbooks. This study investigates how social awareness is represented in English for Nusantara Grade IX, an Indonesian junior high school English textbook, by using the Collaborative for Academic, Social, and Emotional Learning (CASEL) framework. Employing qualitative content analysis, the study analysed both verbal elements, including dialogues, narratives, instructions, and tasks, and visual elements, including illustrations and photographs. The findings identified 215 instances of social awareness, of which 173 instances (80.5%) were verbal and 42 instances (19.5%) were visual. The most frequent sub-skills were taking others’ perspectives (54 instances) and recognising situational demands and opportunities (52 instances), while showing concern for the feelings of others (9 instances) and identifying diverse social norms, including unjust ones (10 instances), appeared least frequently. The findings indicate that the textbook strongly emphasises interpersonal understanding and adaptability, mainly through context-rich dialogues and narratives, while visual elements play a supportive rather than independent role. The study concludes that although the textbook meaningfully incorporates social awareness, its representation remains uneven. More balanced integration across all CASEL sub-skills, especially those related to emotional care, diversity, and unjust social norms, is needed to better support holistic SEL development in English language learning.